Oligosarcus amome (Ostariophysi: Characidae), a new species from the río Uruguay basin, Misiones, Argentina - Almirón, Adriana; Casciotta, Jorge; Piálek, Lubomír; Doubnerová, Klára; Říčan, Oldřich (Zootaxa, 2015)
Oligosarcus amome is described from tributaries of the arroyo Yabotí-Guazú, río Uruguay basin, Misiones Province, Argentina. This new species can be distinguished from all its congeners by the following combination of characters: presence of two conspicuous series of teeth on premaxilla bearing pentacuspidate teeth in the outer series. Oligosarcus amome is the sister taxon of all remaining analyzed species of the genus excepting O. itau.